The process of dramaturgy a handbook - Irelan, Scott R.; Fletcher, Anne 1953-; Dubiner, Julie Felise 1969- (Newburyport, MA Focus Publishing/R. Pullins, Co., 2010)
This book offers a series of workable strategies and practical exercises meant to develop and improve the skills needed during the practice of production dramaturgy.
Pt. 1: Pre-production. Laying the groundwork -- Opening a dialogue -- Conceptual sets -- Pt. 2: Rehearsals. An eye for continuity -- The new play -- Pt. 3: In production. Outreach and education -- A case study of Biloxi Blues -- Closing thoughts -- Appendices: Theatrical-isms -- Sample syllabus.
Includes bibliographical references (pages 147-150).
Keywords: Theater -- Production and direction -- Handbooks, manuals, etc; Drama -- Technique -- Handbooks, manuals, etc; Dramaturges -- Handbooks, manuals, etc